2015
DOI: 10.1093/femsec/fiv120
|View full text |Cite
|
Sign up to set email alerts
|

Tricholoma vaccinumhost communication during ectomycorrhiza formation

Abstract: The genome sequence of Tricholoma vaccinum was obtained to predict its secretome in order to elucidate communication of T. vaccinum with its host tree spruce (Picea abies) in interkingdom signaling. The most prominent protein domains within the 206 predicted secreted proteins belong to energy and nutrition (52%), cell wall degradation (19%) and mycorrhiza establishment (9%). Additionally, we found small secreted proteins that show typical features of effectors potentially involved in host communication. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…The genome sequence of T . vaccinum GK6514 [34] was used to obtain hydrophobin sequences from all strains (NCBI GenBank accession numbers: Supporting Table 2 in S1 File). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome sequence of T . vaccinum GK6514 [34] was used to obtain hydrophobin sequences from all strains (NCBI GenBank accession numbers: Supporting Table 2 in S1 File). …”
Section: Methodsmentioning
confidence: 99%
“…Here, we aimed at investigating differential expression of hydrophobins using of all nine hydrophobin genes of T . vaccinum [34]. The expression patterns allowed us to infer potential roles for each of the hydrophobins in this fungus which mainly grows as a dikaryon.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest enzymatic capabilities of symbiotic fungi such as ecto-ericoid mycorrhizal fungi to produce lignolytic and cellulolytic enzymes (Wagner 2015). Furthermore, (Jumpponen and Trappe; have reported that the enzymatic capabilities of mycorrhizal fungi require lignolytic and cellulolytic enzymes to facilitate penetration through host cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide mass fingerprints and peptide fragmentation fingerprints were used for data analyses based on database constructed from the genome sequence of T. vaccinum (http://genome.jgi-psf.org, ID 59711, Wagner et al ., ) using P rotein S cape 3.0 (Protagen) in combination with mascot 2.3 (Matrix Sciences, U.K.) with following parameters: fixed modification for carbamidomethyl derivates and variable one for the oxidation of methionine, mass values monoisotopic, a peptide mass tolerance of 100 ppm and one missed cleavage. A significant Mascot score higher than 60 was required for successful protein identification.…”
Section: Methodsmentioning
confidence: 99%